2010
DOI: 10.1177/1090820x09360700
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Outcomes Involving Highly Cohesive, Form-Stable Breast Implants From Two Manufacturers in Patients Undergoing Primary Breast Augmentation

Abstract: Provided that there is adherence to core principles and avoidance of errors in planning, patient expectations, and surgery, highly cohesive, form-stable breast implants can deliver excellent long term outcomes in primary breast augmentation in a diverse patient population. The impact of quality processes such as Toyota Production System and Lean Manufacturing was substantive in delivering operational excellence in primary breast augmentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…These data corroborated previously published data, which demonstrated that the Natrelle 410 implants have low rates of wrinkling compared with othershaped implants. Indeed, in a comparative study, Jewell and Jewell 29 reported a 5-fold higher rate of rippling in the CPG implant group compared with the 410 implant group. In a separate study of the 410 implant, wrinkling was reported in 5% of subjects after a mean of 8 years.…”
Section: Discussionmentioning
confidence: 99%
“…These data corroborated previously published data, which demonstrated that the Natrelle 410 implants have low rates of wrinkling compared with othershaped implants. Indeed, in a comparative study, Jewell and Jewell 29 reported a 5-fold higher rate of rippling in the CPG implant group compared with the 410 implant group. In a separate study of the 410 implant, wrinkling was reported in 5% of subjects after a mean of 8 years.…”
Section: Discussionmentioning
confidence: 99%
“…The lessons that I learned in these studies demonstrated that the process of breast augmentation would fit into a standardized planning and quality program similar to the Toyota Production System. 13,16 The results of this outcomes analysis/improvement process in my own clinic have been very gratifying in terms of yielding low reoperation rates and extremely high patient satisfaction. Reoperation must be minimized because any reoperation implies that there was a problem with the outcome.…”
Section: Improving Augmentation Outcomesmentioning
confidence: 96%
“…[11][12][13] These devices represent an opportunity for surgeons to produce better long-term outcomes with lower incidences of adverse events, typical of the studies published for round, smooth implants.…”
Section: : the Anatomically Shaped Form-stable Eramentioning
confidence: 99%
See 1 more Smart Citation
“…This led to high re-intervention rates for patient's dissatisfaction with implant size and other post-operative complications (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%